Experiences of central child health services teams regarding a special governmental investment in child health services - Sergio Flores; Anna Sarkadi (BMC, 2024)
Abstract Background Historically marked by a high infant mortality rate, Sweden's healthcare reforms have successively led to a robust, decentralized universal child health system covering over 97% of the population 0-5 years. However, inequities in health have become an increasing problem and the public health law explicitly states that health inequities should be reduced, resulting in various government initiatives. This study examines the experiences of Central Child Health Services (CCHS) teams during the implementation of the Child Health Services Accessibility Agreement between the State and the regions starting in 2017. The agreement aimed to enhance child health service accessibility, especially in socio-economically disadvantaged areas, but broadly stated guidelines and the short-term nature of funding have raised questions about its effectiveness. The aim of this study was to understand the experiences of CCHC teams in implementing the Child Health Services Accessibility Agreement, focusing on investment decisions, implementation efforts, as well as facilitators and barriers to using the funds effectively. Methods CCHC teams were purposefully sampled and invited via email for interviews, with follow-ups for non-respondents. Conducted from January to October 2023, the interviews were held digitally and recorded with individuals familiar with the agreement's implementation within these teams. Both authors analyzed the transcripts thematically, applying Braun and Clarke's framework. Participants represented a cross-section of Sweden's varied healthcare regions. Results Three main themes emerged from the thematic analysis: "Easy come, easy go," highlighting funding uncertainties; "What are we supposed to do?" expressing dilemmas over project prioritization and partner collaboration; and "Building castles on sand," focusing on the challenges of staff retention and foundational program stability. Respective subthemes addressed issues like fund allocation timing, strategic decision-making, and the practical difficulties of implementing extended home visiting programs, particularly in collaboration with social services. Conclusions This study uncovered the challenges faced in implementing the Child Health Services Accessibility Agreement across different regions in Sweden. These obstacles underline the need for precise guidelines regarding the use of funds, stable financing for long-term project sustainability, and strong foundational support to ensure effective interprofessional collaboration and infrastructure development for equitable service delivery in child health services.